Acceptance of screening for Intimate Partner Violence, actual screening and satisfaction with care amongst female clients visiting a health facility in Kano, Nigeria - Ime A. John; Stephen Lawoko; Abimbola Oluwatosin (AOSIS, 2011)
Background: Healthcare providers have advocated for the screening and management of Intimate Partner Violence (IPV) against women and its consequences. Unfortunately, data from high income countries suggest that women may have varied preferences for being screened for IPV in healthcare. Although women's preference for screening in sub-Saharan countries has not been well researched, IPV remains an accepted societal norm in many of these countries, including Nigeria. Objective: The objective of the study was to assess women's acceptance of screening for IPV in healthcare, the extent to which inquiry about IPV was carried out in healthcare and whether such inquiry impacted on satisfaction with care. Method: Data on these variables were gathered through structured interviews from a sample of 507 women at a regional hospital in Kano, Nigeria. The study design was cross-sectional. Results: The results found acceptance for screening in the sample to be high (76%), but few women (7%) had actually been probed about violence in their contact with care providers. Acceptance for screening was associated with being married and being employed. Actual screening was associated with ethnicity and religion, where ethnic and religious majorities were more likely to be screened. Finally, being screened for IPV seemed to improve satisfaction with care. Conclusion: The findings demonstrate the need for adaptation of a screening protocol that is also sensitive to detect IPV amongst all ethnic and religious groups. The findings also have implications for further education of socio-economically disadvantaged women on the benefits of screening.